Genomic and virologic characterization of samples from a shipboard outbreak of COVID-19 reveals distinct variants within limited temporospatial parameters - Cer, Regina Z.; Voegtly, Logan J.; Adhikari, Bishwo N.; Pike, Brian L.; Lueder, Matthew R.; Glang, Lindsay A.; Malagon, Francisco; Ana, Ernesto Santa; Regeimbal, James M.; Potts-Szoke, Maria F.; Schully, Kevin L.; Smith, Darci R.; et al. (Frontiers in Microbiology, 2022)
Early in the pandemic, in March of 2020, an outbreak of COVID-19 occurred aboard the aircraft carrier USS Theodore Roosevelt (CVN-71), during deployment in the western Pacific. Out of the crew of 4,779 personnel, 1,331 service members were suspected or confirmed to be infected with SARS-CoV-2. The demographic, epidemiologic, and laboratory findings of service members from subsequent investigations have characterized the outbreak as widespread transmission of virus with relatively mild symptoms and asymptomatic infection among mostly young healthy adults. At the time, there was no available vaccination against COVID-19 and there was very limited knowledge regarding SARS-CoV-2 mutation, dispersal, and transmission patterns among service members in a shipboard environment. Since that time, other shipboard outbreaks from which data can be extracted have occurred, but these later shipboard outbreaks have occurred largely in settings where the majority of the crew were vaccinated, thereby limiting spread of the virus, shortening duration of the outbreaks, and minimizing evolution of the virus within those close quarters settings. On the other hand, since the outbreak on the CVN-71 occurred prior to widespread vaccination, it continued over the course of roughly two months, infecting more than 25% of the crew. In order to better understand genetic variability and potential transmission dynamics of COVID-19 in a shipboard environment of immunologically naïve, healthy individuals, we performed whole genome sequencing and virus culture from eighteen COVID-19 positive swabs collected over the course of one week. Using the unique variants identified in those genomes, we detected seven discrete groups of individuals within the population aboard CVN-71 infected with viruses of distinct genomic signature. This is in stark contrast to a recent outbreak aboard another U.S. Navy ship with >98% vaccinated crew after a port visit in Reykjavik, Iceland where the outbreak lasted only approximately two weeks and the virus was clonal. Taken together, these results demonstrate the utility of sequencing from complex clinical samples for molecular epidemiology and they also suggest that a high rate of vaccination among a population in close communities may greatly reduce spread, thereby restricting evolution of the virus.